Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1371/journal.pone.0023977
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of TgPhIL1 in Toxoplasma gondii Results in Altered Parasite Morphology and Fitness

Abstract: The inner membrane complex (IMC), a series of flattened vesicles at the periphery of apicomplexan parasites, is thought to be important for parasite shape, motility and replication, but few of the IMC proteins that function in these processes have been identified. TgPhIL1, a Toxoplasma gondii protein that was previously identified through photosensitized labeling with 5-[125I] iodonapthaline-1-azide, associates with the IMC and/or underlying cytoskeleton and is concentrated at the apical end of the parasite. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Consistent with this, our chemical proteomic approach identified PhIL1, which has been previously implicated in parasite morphology (Barkhuff et al, 2011), as being palmitoylated. We metabolically labeled parasites expressing a GFP-tagged PhIL1 (Gilk et al, 2006) with 17-ODYA.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with this, our chemical proteomic approach identified PhIL1, which has been previously implicated in parasite morphology (Barkhuff et al, 2011), as being palmitoylated. We metabolically labeled parasites expressing a GFP-tagged PhIL1 (Gilk et al, 2006) with 17-ODYA.…”
Section: Resultssupporting
confidence: 80%
“…We biochemically confirm the palmitoylation of several candidates from our proteomic analysis, including Myosin Light Chain 1 (MLC1) and Myosin A (MyoA), components of the glideosome, the parasite's motility complex (Herm-Gotz et al, 2002; Meissner et al, 2002). We confirm that the morphology-associated photosensitized INA-labeled protein (PhIL1) (Barkhuff et al, 2011; Gilk et al, 2006) is palmitoylated. Unexpectedly, we found that Apical Membrane Antigen 1 (AMA1), a protein that functions during invasion (Hehl et al, 2000; Lamarque et al, 2014; Mital et al, 2005), is palmitoylated.…”
Section: Introductionsupporting
confidence: 70%
“…At the present time, no alveolin proteins have been disrupted in T. gondii and so any potential functional redundancy within this family is currently unknown. However, the IMC-associated protein TgPhIL1 has been deleted, resulting in viable parasites which were shorter and wider than the wild type, although with no observable ultrastructural IMC defect (Barkhuff et al, 2011). These mutants replicated normally, but had subtly impaired motility and a fitness defect in mixed infection (Gilk et al, 2006;Barkhuff et al, 2011;Leung et al, 2014).…”
Section: Biogenesis Of the Inner Membrane Complex In T Gondiimentioning
confidence: 99%
“…The meshwork component IMC15 is also enriched in the apical cap (Anderson-White et al, 2011). Another protein, which is not essential, localizing predominantly to the apical cap is Photosensitized INA-labeled protein 1 (PhIL1) (Barkhuff et al , 2011; Gilk et al , 2006). Finally, a component of the glideosome, gliding-associated protein 70 (GAP70), localizes specifically to the apical cap (Fig.…”
Section: Composition Of the Cytoskeletonmentioning
confidence: 99%